Evasão escolar de jovens e adultos em uma escola pública de Santo André - Buzeto, Elizete Cristina Carnelós (2020)
Youth and Adult Education in Brazil is a public policy that aims to provide access and permanence to school for those who could not exercise this right at the expected age and is related to the promotion of human development, the reduction of social and social inequalities. compliance with social rights. The contextualized research of reality reveals a great challenge to be overcome in this educational modality, which is school dropout, the object of this research, in a public school in Santo André, state of São Paulo, whose objective is to verify the reason for school dropout. Youth and Adult Education. As specific objectives, we list: understand the reasons that lead students to drop out of school and check the needs and suggestions they present for the qualification of Youth and Adult Education. We started from the hypothesis that school dropout is associated with structure and organization and with personal issues, as students have low interest in school, not choosing to continue their studies as a life priority. The methodology will be of a qualitative and documentary nature and, as instruments of data collection, participant observation will be applied, the semi-structured interview with students and educators and analysis of the official school documents, related to Youth and Adult Education, such as enrollment, class diary, school history and cycle council minutes. As an intervention proposal, we will socialize the result of the research with the teaching and student staff of that school, proposing a dialogue between the subjects to raise awareness of the context, the needs and possibilities for change, and deliver a copy to the Department of Education. of the dissertation.To support the youth and adult categories as conscious and critical subjects, education as a right and public policies, we will use the authors of Critical Pedagogy; in the category of construction of Youth and Adult Education in the municipality of Santo André the publications of the Municipal Network of Santo André; in the legislation category, we will use education standards, such as: Law of Guidelines and Bases, Opinion of the National Education Council, National Curriculum Guidelines for Basic Education, National Education Plan and Municipal Education Plan of Santo André. As previous conclusions of the research, it can be pointed out that among the causes of school dropout in the 1st Term of Youth and Adult Education are personal factors, namely, the need for paid work, learning difficulties, low self-esteem and criticality and lack of perspectives of personal and economic overcoming, financial factors, such as the poor distribution of financial resources among the teaching modalities and structural and pedagogical factors in the school environment, which do not provide the exercise of criticality.